Art and the Young Child Another Look at the Developmental Question - Golomb, Claire ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1992)
A study of young children's art and representational thought investigated the order in which representational concepts emerge in children's modeling in clay. It was predicted that children's three-dimensional representations of simple, symmetrical, and balanced familiar objects would be superior to their representations of complex, asymmetrical, unbalanced, and unfamiliar objects. Eight modeling tasks, including the modeling of objects, animals, and humans, were administered to 109 children between 4 and 13 years of age and to 18 college students. Subjects' actions and verbalizations were recorded, and their sculptures were scored. Findings indicated that a restructuring is likely to occur in the way children approach a modeling task as they develop greater cognitive maturity. Young children first make use of three-dimensional representational concepts in the modeling task. They later develop seemingly two-dimensional strategies when their ambition to create closer likenesses and more complex figures conflicts with the technical difficulties they encounter in manipulating the clay medium. Cognitive maturity in itself does not automatically result in competence; practice and motivation are crucial. Findings also highlighted preschoolers' sensitivity to the demands of a task and their capacity to experiment with diverse solutions. Implications for the teaching of art are discussed. A list of 27 references and pictures of 14 clay sculptures of the children and college students are included. (SLD)
ERIC Note: Paper presented at the Making Meaning through Art Conference (Urbana, IL, September 17-19, 1992). Illustrations are marginally legible.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Age Differences; Art Education; Art Expression; Children; Cognitive Development; Cognitive Processes; College Students; Comparative Analysis; Concept Formation; Developmental Psychology; Early Childhood Education; Elementary Secondary Education; Higher Education; Sculpture; Dimensional Representation; Representational Competence; Reports, Research; Speeches/Meeting Papers